Reducing Premature Mortality from Cardiovascular and Other Non-Communicable Diseases by One Third: Achieving Sustainable Development Goal Indicator 3.4.1 - Thomas R. Frieden; Laura K. Cobb; Robynn C. Leidig; Sumi Mehta; Daniel Kass (Ubiquity Press, 2020)
Non-communicable diseases (NCDs) are the world's leading causes of death and disability, with cardiovascular disease (CVD) accounting for half of NCD deaths. An ambitious global target established by the United Nations Sustainable Development Goals - indicator 3.4.1 - aims to reduce the risk of premature death among people aged 30-69 years from CVD, cancer, diabetes, and chronic lung disease by one third by 2030. This article reviews the science and practice informing what is required to achieve this target, identifying seven interventions that can accelerate progress: 1) tobacco control; 2) treatment to reduce cardiovascular risk; 3) reduction of dietary sodium; 4) reduction of household air pollution; 5) elimination of artificial trans fat; 6) reduction of alcohol use; and 7) prevention, detection, and treatment of cancers. Achieving the target is possible - there has already been progress in some areas, particularly related to CVD reduction - but only if there is faster, more concerted action.